Red & Green - Ehlert, Lois (New York : Beach Lane Books, 2023)
On a cold, snowy night, all is quiet throughout the house except for a small, michievous mouse.
new kids book 2023 fall.
Ages 3-8.
Grades K-1.
Keywords: Stories in rhyme; Christmas -- Fiction; Mice -- Fiction; Stories in rhyme; Picture books; Christmas fiction